Examining the Determinants of Iranian Students' Use of Mobile Phones during Lecture Periods - Mortazavi, Mohsen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Technologies are affecting student’s involvement, motivation, and efficiency in education. Mobile phones as the most popular technological devices have educational capabilities. For example, they can provide students with meaningful learning opportunities through a variety of applications and access to the internet. Using such skills is regarded as an aspect of developing 21st century skills. Despite the numerous helpful features of mobile phones, they are believed to result in distractions, disruptions, cheating and untimely use. However, the students' persistence in using mobile phones during lessons even when forbidden has become a concerning issue. Therefore, the present study was proposed to examine the causes of 130 Iranian students' utilize of mobile phones during the classrooms in the Faculty of Pharmacy at EMU in the Turkish Republic of Northern Cyprus (TRNC). A comparison was made among students' perception with regard to their age, gender, and grades. Students' perception was evaluated using a questionnaire which addressed six factors: boredom, emergency, perceived behavioral control, addiction, social connection, and class-related use. A quantitative research method was used and frequencies, ANOVA and t-test were performed to analyze the data. The results of the study showed that most of the students had a tendency to utilize mobile phones during lessons in order to class-related use. Moreover, whereas no statistically significant differences were found among students' perception with regard to their gender and grade variables, significant differences were found in relation to the age variable. The study had important implications for instructors and practitioners in this field of inquiry. Keywords: Mobile phones use, performance, university students, classroom

ÖZ : Teknoloji, öğrencilerin eğitime olan katılımlarını, motivasyonlarını ve verimliliklerini etkilemektedir. En popüler teknolojil cihaz olan cep telefonları, eğitime de yarar sağlamaktadır. İnternet bağlantısı ve birçok uygulama olanağı sağlayan bu cihazlar, öğrencilere yararlı öğrenim olanakları sağlayabilmektedirler. Bu unsurları kullanmak 21. yüzyıla özgü yetenekleri geliştirmede bir etken olarak görülmektedirler. Bu sayısız faydanın yanı sıra cep telefonlarının; dikkat dağıtma, karışıklığa itme, hile ve uygun zamanda kullanmama gibi sonuçlar doğuracağı düşünülmektedir. Yasak olmasına rağmen, öğrencilerin sınıflarda cep telefonlarını kullanmalarındaki ısrarı bir sorun haline gelmektedir. Bu yüzden, bu araştırmada Kuzey Kıbrıs Türk Cumhuriyeti’nde bulunan Doğu Akdeniz Üniversitesi (DAÜ) Eczacılık Fakültesi’nde okuyan 130 İranlı öğrenci üzerinde, sınıfta cep telefonu kullanımlarını inceleme yapılmıştır. Öğrencilerin; yaş, cinsiyet ve sınıfları göz önüne alınarak, görüşleri üzerinde bir karşılaştırma yapılmış ve sıkılma, acil durum, algılanan davranışsal kontrol, bağımlılık, sosyal bağ ve dersle ilintili kullanımından oluşan 6 unsuru barındıran bir anket öğrencilerin görüşlerini ölçmek için kullanılmıştır. Nicel araştırma tekniği, (frequency) sıklık tablosu, varyans analizi ve t-testi bilgileri ölçmek için uygulanmıştır. Cinsiyet ve sınıf farklılıkları söz konusuyken öğrencilerin görüşleri arasında statiksel bir fark saptanmamış, fakat yaş etkeninde farklılıklar ortaya çıkmıştır. Anahtar Kelimeler: Cep telefonları kullanımı, performans, üniversite öğrencileri, sınıf
Master of Science in Information and Communication Technologies in Education. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Education, Dept. of Information and Communication Technology in Education, 2016. Supervisor: Dr. Fatma Tansu Hocanın.
Keywords: Information and Communication Technology in Education; Computer - assisted instruction - Computer programs; Mobile Phones - Usage - Classroom; Mobile phones use; performance; university students; classroom